Integration of water management in the assessment of the impact of heavy metals discharge from the power plant with mitigation strategies - Olha Biedunkova; Pavlo Kuznietsov (Ecological Indicators)
This study investigates the levels of heavy metal (HM) contamination in the Styr River, focusing on the potential impact of water discharges from a power plant. Sampling was conducted at two sites over four years, assessing the presence of HMs such as zinc, cadmium, lead, copper, nickel, manganese, arsenic, and chromium. Results indicate that HM concentrations at both locations comply with international and national permissible levels, suggesting minimal pollution. However, the study highlights the importance of continuous monitoring and the implementation of mitigation strategies to address the potential long-term effects of industrial discharges on aquatic ecosystems. The research emphasizes the necessity for an integrated approach, combining advanced technologies and regulatory frameworks, to effectively manage water quality and protect ecological health. The findings advocate for enhanced water management practices to mitigate the impact of HMs and ensure sustainable aquatic environments.